Construction of carbon-based flame retardant composite with reinforced and toughened property and its application in polylactic acid. Issue 34 (10th August 2022) - Xiao, Yunchao; Yang, Yaru; Luo, Qiulan; Tang, Bolin; Guan, Jipeng; Tian, Qiang
Abstract : A CNT-based flame retardant was synthesized and introduced into PLA to simultaneously improve the flame retardancy, strength and toughness of PLA. Abstract : To simultaneously improve the flame retardancy, strength and toughness of polylactic acid (PLA) fibers, a composite flame retardant CNTs-H-C was prepared with carbon nanotubes (CNTs) as the core, hexachlorocyclotriphosphazene as linker, and chitosan grafted on the surface. The prepared CNTs-H-C was introduced into a PLA matrix to obtain CNTs-H-C/PLA composites and fibers via a melt-blending method. The morphology, structure, flame retardant properties and mechanical properties were thoroughly characterized, and the flame retardant mechanism was studied. Results showed that the prepared CNTs-H-C displayed a nanotube-like morphology with good compatibility and dispersion in the PLA matrix. After blending with PLA, CNTs-H-C/PLA composites exhibited outstanding flame retardancy with limiting oxygen index (LOI) increasing from 20.0% to 27.3%, UL94 rating reaching V-0. More importantly, the introduction of CNTs-H-C did not affect the spinnability of PLA. Compared with pure PLA fibers, the LOI of CNTs-H-C/PLA fibers with a CNTs-H-C content of 1.0 wt% increased by 32.5%, and meanwhile the breaking strength and elongation increased by 28.2% and 30.4%, respectively. Mechanism study revealed that CNTs-H-C/PLA possessed a typical condensed phase flame retardancy mechanism. In short, we have developed a CNT-based composite flame retardant with reinforced and toughened properties for the PLA matrix. The prepared CNTs-H-C showed great potential in polymer flame retardancy and mechanical enhancement.